(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In common usage the word “myth” refers to narratives or beliefs that are untrue or merely fanciful; the stories that make up national or ethnic mythologies describe characters and events that common sense and experience tell us are impossible. The universality of myth emerges, however, when we make comparisons between mythologies. Through comparison certain constants appear. Most mythologies which is to say, religions have deities, most have heroes who perform certain ritual deeds, many of which are found in most mythologies the quest, the descent to the Underworld. Universal patterns or common motifs in mythology have been called archetypal, that is, reflective of psychological tendencies that are common to the human species as a whole. At the archetypal level a story such as the resurrection of Jesus becomes true freed of the parochial restrictions of the merely local when compared to other resurrection stories such as those of Osiris or Persephone. Through comparison, the truth of the story is seen to lie in the concept of resurrection rather than in the individuals who are resurrected. Having said that, it is again important to remember that archetypes those of the heroes’ quest or the supreme deity or the trickster or the Flood, or creation itself only take on life and meaning when they are clothed in cultural particularity.